2015
DOI: 10.1017/s1742170515000320
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of grapevines to biodynamic management

Abstract: A 3-year (2011–2013) field trial was carried out in a mature vineyard (Vitis vinifera L., cv. Sangiovese), planted in 2003, to assess physiological responses of grapevines to biodynamic management. Starting in 2007, the vineyard was managed with organic production protocols in accordance with EC Regulations (834/2007). In 2008, the vineyard (2 ha) was divided in two large plots, with each plot having similar soil physico-chemical properties. One of the plots was managed with organic protocols per EC Regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 54 publications
3
24
0
2
Order By: Relevance
“…Regarding to yields, both Reeve, et al (2005) and Botelho, et al (2015) detected similar values when the organic cultivated vines where compared to the biodynamic ones. In addition, Döring, et al (2015) observed similar yields in vines under biodynamic and organic farming; however, these cultivation methods showed lower values when compared to the integrated management.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Regarding to yields, both Reeve, et al (2005) and Botelho, et al (2015) detected similar values when the organic cultivated vines where compared to the biodynamic ones. In addition, Döring, et al (2015) observed similar yields in vines under biodynamic and organic farming; however, these cultivation methods showed lower values when compared to the integrated management.…”
Section: Introductionmentioning
confidence: 74%
“…Few scientific studies have been devoted to understand the effects of biodynamic preparations/method on plant physiology and yield (Botelho, Roberti, Tessarin, Garcia-Mina, & Rombolà, 2015;Collins, Penfold , Johnston, Marschner, & Bastian, 2015;Döring, Frisch, Tittmann, Stoll, & Kauer, 2015;Rombolà, Tassarin, Tumbarello, Parpinello, & Versari, 2015), edible parts composition and nutritional value (Turinek, Grobelnik-Mlakar, Bavec, & Bavec, 2009). Recently it has been reported that some biodynamic preparations led to an increase in leaf enzymatic activities of chitinase and β-1,3-glucanase, which are typically correlated with plant biotic and abiotic stresses and associated with induced plant resistance (Botelho, et al, 2015;Reeve, Carpenter-Boggs, Reganold, York, McGourty, & McCloskey, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além da amostragem de solos realizada no início do experimento em 2008, já descrita acima e apresentadas abaixo na Tabela 1 por Botelho et al (2015), foram realizadas durante o ano de 2012 duas coletas de amostras de solos, sendo a primeira na primavera, em maio, durante a fase de florescimento e a segunda no outono, em setembro, na fase de maturação.…”
Section: Coleta De Amostras De Solounclassified
“…A constituição de cada preparado é descrita por Botelho et al (2015), conforme análises laboratoriais realizadas com os produtos adquiridos e aplicados no mesmo experimento.…”
Section: Preparados Biodinâmicosunclassified